Replication‐coupled histone H3.1 deposition determines nucleosome composition and heterochromatin dynamics during Arabidopsis seedling development. Issue 1 (13th June 2018) - Benoit, Matthias; Simon, Lauriane; Desset, Sophie; Duc, Céline; Cotterell, Sylviane; Poulet, Axel; Le Goff, Samuel; Tatout, Christophe; Probst, Aline V.
Summary: Developmental phase transitions are often characterized by changes in the chromatin landscape and heterochromatin reorganization. In Arabidopsis, clustering of repetitive heterochromatic loci into so‐called chromocenters is an important determinant of chromosome organization in nuclear space. Here, we investigated the molecular mechanisms involved in chromocenter formation during the switch from a heterotrophic to a photosynthetically competent state during early seedling development. We characterized the spatial organization and chromatin features at centromeric and pericentromeric repeats and identified mutant contexts with impaired chromocenter formation. We find that clustering of repetitive DNA loci into chromocenters takes place in a precise temporal window and results in reinforced transcriptional repression. Although repetitive sequences are enriched in H3K9me2 and linker histone H1 before repeat clustering, chromocenter formation involves increasing enrichment in H3.1 as well as H2A.W histone variants, hallmarks of heterochromatin. These processes are severely affected in mutants impaired in replication‐coupled histone assembly mediated by CHROMATIN ASSEMBLY FACTOR 1 (CAF‐1). We further reveal that histone deposition by CAF‐1 is required for efficient H3K9me2 enrichment at repetitive sequences during chromocenter formation. Taken together, we show that chromocenter assembly during post‐germination development requires dynamic changes in nucleosome composition and histone post‐translational modifications orchestrated by the replication‐coupled H3.1 deposition machinery.